Type 2 diabetes as a factor influencing the professional activity of patients after acute coronary syndrome - Niedziałek, Jarosław; Mizerski, Grzegorz; Gorczyca, Rafał; Jaroszyński, Andrzej; Zagórski, Jerzy (Polish Journal of Public Health, 2012)
Introduction. Type 2 diabetes (Diabetes mellitus typus 2 – DM t.2) is a civilization disease of a social character exerting health and socio-economic effects difficult to overestimate. Diabetes deteriorates the course of many diseases, especially those of a cardiovascular nature. Aim. The objective of the presented study was determination of the effect of type 2 diabetes on the occupational activity of patients who had undergone an Acute Coronary Syndrome (ACS). Material and methods. The study covered 8,640 patients who had undergone an ACS (5,642 males and 2,998 females) treated at the Spa Sanatorium for Farmers in Nałęczów during the period 2005-2009. Results. Among those who had undergone an ACS and had been occupationally active before the event, there were 50.4% of patients with diabetes and 56.7% without diabetes (p<0.001). According to age, the percentage of patients who had been occupationally active before the occurrence of an ACS was 60.8% of males with diabetes and 61.6% without diabetes (p=0.65), and 37.5% of females with diabetes and 46.7% without diabetes (p<0.001). After undergoing an ACS, 20.1% of patients with diabetes and 28.8% of those without diabetes remained occupationally active (p<0.001). This percentage among males was 27.9 % with diabetes and 35.2% without diabetes, respectively (p<0.001), while among females – 10.6% with diabetes and 15.7 % without diabetes (p<0.001). Conclusions. Diabetes significantly more frequently leads to the necessity for discontinuing occupational activity in males than females with a history of ACS, compared to patients without diabetes. Primary and secondary prophylaxis of diabetes could contribute to the reduction of social costs caused by the lack of occupational activity among patients.